1995
DOI: 10.1677/joe.0.1450097
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin antagonists delay the initiation of parturition and prolong its active phase in rats

Abstract: The physiological importance of oxytocin for the initiation and maintenance of labour and delivery is controversial. We investigated the effects of two novel peptide oxytocin antagonists on the onset and the progress of delivery in rats implanted with a jugular vein cannula one day before term. During delivery rats were given either an oxytocin antagonist (OVT16, n = 10, or F382, n = 7, 30 micrograms/kg) or vehicle (n = 10, 9) after the birth of the second pup and the time to deliver five more pups was recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…Moreover, there is significant increase in uterine sensitivity to OT via upregulation of OTR in both rats and humans during the onset of labour [12][13][14]. Additionally studies in rats [15][16][17], non-human primates [18][19][20] and in humans [21,22] reported that OT antagonists can inhibit late gestational uterine contractions and the process of parturition. The role of OT varies between different animal species.…”
Section: Previously Established Roles Of Ot/otr Systemmentioning
confidence: 99%
“…Moreover, there is significant increase in uterine sensitivity to OT via upregulation of OTR in both rats and humans during the onset of labour [12][13][14]. Additionally studies in rats [15][16][17], non-human primates [18][19][20] and in humans [21,22] reported that OT antagonists can inhibit late gestational uterine contractions and the process of parturition. The role of OT varies between different animal species.…”
Section: Previously Established Roles Of Ot/otr Systemmentioning
confidence: 99%
“…It is high relevant between premature delivery and oxytocin, QSAR study on oxytocin peptides and homologous antagonist design are both valuable in theories and the applications to premature delivery. [23][24] A set of 21 oxytocin peptides was also used to test the descriptors predictability, their bioactivities scales were intensity uterine contraction of mice. 25 Each oxytocin peptide contains 3 amino acids, and the structural information of each peptide was quantified by 24 variables.…”
Section: Qsar Analysis On Oxytocin Peptidesmentioning
confidence: 99%
“…During parturition, one-third of oxytocin stores in the pituitary are depleted (Fuchs & Saito 1971), and if oxytocin function is impaired, parturition is slowed or ceases completely (Antonijevic et al 1995a(Antonijevic et al , 2000. In mice and rats, treatment with an oxytocin antagonist slows parturition, while exogenous oxytocin treatment during impaired parturition can rescue normal parturition (Antonijevic et al 1995b, Douglas et al 2002.…”
Section: Introductionmentioning
confidence: 99%